Exploiting sweetpotato as an animal feed in East Africa - International Potato Center (2011)
Sweetpotato offers great potential as animal feed. But in in contrast to China, where 25-30% of sweetpotato is used as animal feed, its potential as feed or as a dual purpose crop (food and feed) has not been fully exploited in Sub-Saharan Africa. Early results from this project have identified “best bet” varieties for dual purpose and forage uses with pigs and dairy cattle, along with promising silage blends for boosting feed supply and nutrition.